Latent Tuberculosis Infection among Household Contacts of Tuberculosis Patients, Healthcare Workers, and Tuberculosis Patients Using QuantiFERON-tuberculosis Gold Plus and Tuberculin Skin Test in a Tertiary Care Hospital Setting Bhubaneswar, Odisha – A Cross-sectional Study - Braja Sundar Barik; Chinmay Divyadarshi Kar; Shritam Das; Tahziba Hussain; Sasmita Nayak; Arun Kumar Sahu; Sooman Sundaray; Sanghamitra Pati (Journal of Global Infectious Diseases)
Introduction: Contacts of tuberculosis (TB) patients have an increased risk of latent TB infection (LTBI). Currently, it is diagnosed using one of the two methods: Tuberculin skin test (TST) or QuantiFERON-TB Gold Plus. This study aims to estimate the concordance of TST and QFT-TB Gold Plus and associated factors among 73 healthcare workers (HCWs) and 172 household contacts (HHCs) who came in contact with active TB patients. This study was conducted from January to June 2023. Methods: Prevalence and agreement were calculated. A regression analysis was performed to assess the predictors of discordance factors. Results: The prevalence of latent TB was 20.40% (n = 50), defined as a positive result on either test. The overall agreement among participants was 62.04%, with a kappa coefficient of 0.26 (0.16–0.36, 95% confidence interval [CI]) (McNemar, P < 0.001). A higher risk of LTBI was associated with BCG vaccination history, odd ratio 1.63, (95% CI 0.78–3.43) for TST and 0.51 (95% CI 0.22–1.15) for QFT, but this was not significant. Moreover, in our study, only the body mass index of 18.5–25 kg/m2 yielded an odds ratio of 2.33 (95%CI 0.77–6.47) for TST and 1.72 (95% CI 0.48–6.05) for QFT, was significant. Compared with QFT-TB Gold Plus, the sensitivity and specificity of TST were 80.65 (68.63–89.58) and 55.74 (48.22–63.06). Conclusion: TST exhibited a profound level of agreement with the QFT-Gold Plus assay but showed a higher rate of positivity due to some associated factors among HCWs, HHCs, and TB patients.